A europeização das políticas migratórias portuguesas para extracomunitários - Silva, João Carlos Jarochinski (2014)
Portugal is a country marked by emigration flows. However, with the end of the Colonial Empire, the re-democratization and its entry into the European Community, Portugal has started to receive immigrants, mainly from its former colonies, in search of better opportunities in a country that showed favorable circumstances for said immigrants to settle and improve their lives. In the 1990s, besides the immigrants from former colonies, groups from other locations started to arrive, especially people from Eastern Europe and Asia. In light of this, the topic of migration started to definitively receive attention in the political scene, and Portugal produced a great quantity of norms for regulation of this issue in the end of the 20th century and the beginning of the 21st century. Portugal´s belonging to the European Union, however, brought as a consequence the need of the incorporation of community rules to deal with immigration, be it by people from other Member-states of the EU, be it by people from third states, which started to be called third-country nationals. The latter are, notably, when in irregular situation, victims of a migration logic mainly focused on repulsion, which generates either barriers or the criminalization of the act of migrating. Steaming from this, the present work develops an analysis of the legislative production in the issue of migration in Portugal, highlighting the connection of said legislative production with the history of the migratory flows that marked the country, up to the moment in which state´s regulation begins to be replaced by community rules. The construction of integration in Europe, the incorporation of the migration issue into other topics of the European Union and the most relevant legislative production in this area are also analyzed, especially in terms of their content and production which will be debated. Furthermore, the work posits the specificity of the migratory framework of Portugal in the midst of a comparison with the scenarios of other countries in Southern Europe, which were branded as the Southern European Model of Immigration. The work also discusses striking aspects for migration, as the use of culture for exclusion, the view that immigration is a factor of insecurity, and the media s discourse on immigration and migrants. Thus, by means of the comparative methodology between the Portuguese and European realities, the work assesses the change brought about the Europeization of migratory norms in Portugal, aiming to demonstrate that this shift did not mean an improvement in regulation, given that it does not considered either the specific national context or the interests and external ties of the country, does not offer more efficient means of control, and is based in a standardization that thinks migration with a focus on security and exclusion